(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
Diabetic nephropathy has become a leading cause of end stage renal failure worldwide. To develop Complementary and Alternative Medicine for the treatment of diabetic nephropathy, the present study investigated the protective effects of methanolic extract of Bougainvillea spectabilis (MEBS) in streptozotocin-induced diabetic nephropathy. In this study, diabetes was induced by a single injection of streptozotocin (STZ, 45 mg/kg, i.p.) in rats. STZ diabetic rats were treated with oral doses of MEBS (200 and 400 mg/kg) for 8 weeks. At the end of the experimental period body, kidney weight, blood glucose levels, serum and urine parameters were investigated. Antioxidant enzymes and lipid peroxide levels were determined in the kidney along with histopathological examination of the same. MEBS significantly increased body weight, lowered blood glucose levels and ameliorated kidney hypertrophy index in the STZ-diabetic rats. The extract also decreased the levels of creatinine, blood urea nitrogen, total cholesterol, triglycerides, advanced glycation end products and albumin in serum and urine, respectively. MEBS significantly increased the antioxidant parameters in the kidney. Histological evaluation revealed that MEBS treated STZ-diabetic rats demonstrated reduced vacuolar degeneration of tubules; periodic acid Schiff base (PAS) positivity staining intensity in glomeruli and basement membrane thickening. Present findings provide experimental evidence that MEBS has potential antioxidant, antihyperglycemic and anti-glycation activities which might be helpful in slowing the progression of diabetic nephropathy.